2015
DOI: 10.1101/cshperspect.a021469
|View full text |Cite
|
Sign up to set email alerts
|

The Chimpanzee Model for Hepatitis B Virus Infection

Abstract: Even before the discovery of hepatitis B virus (HBV), it was known that chimpanzees (Pan troglodytes) are susceptible to human hepatitis viruses. The chimpanzee is the only primate animal model for HBV infections. Much like HBV-infected human patients, chimpanzees can developacute andchronic HBVinfectionsand consequent hepatitis. Chimpanzees alsodevelop a cellular immune response similar to that observed in humans. For these reasons, the chimpanzee has proven to be an invaluable model for investigations on HBV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 189 publications
0
42
0
Order By: Relevance
“…Regardless, chimpanzees, owing to their high genetic similarity with humans, have proven to be the most useful model for the study of viral hepatitis mainly because they are susceptible to infection with hepatitis viruses. However, they do not develop a similar spectrum of liver disease as humans do 144,145 . Another interesting caveat is that these primates are monomorphic for several of the polymorphisms in the IL28B gene that have been linked to HCV clinical outcomes 146,147 ; thus, chimpanzees might not be suitable for this line of investigation.…”
Section: Animal Modelsmentioning
confidence: 95%
“…Regardless, chimpanzees, owing to their high genetic similarity with humans, have proven to be the most useful model for the study of viral hepatitis mainly because they are susceptible to infection with hepatitis viruses. However, they do not develop a similar spectrum of liver disease as humans do 144,145 . Another interesting caveat is that these primates are monomorphic for several of the polymorphisms in the IL28B gene that have been linked to HCV clinical outcomes 146,147 ; thus, chimpanzees might not be suitable for this line of investigation.…”
Section: Animal Modelsmentioning
confidence: 95%
“…Across all age groups, however, these figures are 0.89% and 14.8 (4.4~22.3) million, respectively [7]. Currently, there is neither a vaccine nor a post-exposure prophylactic treatment that is effective in preventing HCV infection, largely because of the high genetic diversity among the viral lineages [8]. Longterm isolated circulation has enabled the virus to accumulate variations to evade population immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have found that different degrees of liver brosis are involved in the development and outcome of hepatitis B. [86][87][88][89][90][91] Aer the liver tissue of the model mice was injured, syringin regulated the elevated abnormalities state of LN, HA, and PC in the blood, indicating the trend of liver brosis. IFN is an important biological function cytokine with antiviral, anti-proliferative, and immunomodulatory effects in the body.…”
Section: Discussionmentioning
confidence: 99%